Work Method Improvement Based On Motion Study And Application Of 5s In Lower Casing Assembly Of E-ktp Reader In The Production Department Of Pt Abc - Intan Geovani; Wiyono Wiyono; Marina Yustiana Lubis (eProceedings of Engineering, 2016)
PT ABC is a company that develops business and products in the electronics fields for industry and infrastructure. One of the products produced by PT ABC is E-KTP Reader. Basically, E-KTP Reader consists of two main parts, upper casing and lower casing. Based on observations, process time for each workstation is greater than a predetermined time by the company. The longest process time is in workstation to assemble lower casing. The observation time is 12, 3 minutes and the predetermined time is 5,5 minutes. Work environment is expected as the causes of the long process time. The components are placed in different table with working table. Then, the components for upper and lower casing are not separated and labeled. Motion study and the application of 5S are used to improve work environment. This improvement has been implemented for one times simulation and the process time succesfully reduced for about 249,5 seconds from 740,6 seconds to 491,1 seconds. Keyword : 5S, Motion Study, Work Environment